Financial stability of Vietnam banking system in the context of global crisis 2008-2009 :A thesis submitted as a requirement for the degree of Bachelor of Finance and Banking /Nguyễn Thị Hồng Hạnh ; Nguyễn Quỳnh Anh supervisor. - Nguyễn, Thị Hồng Hạnh.
Khoá luận tốt nghiệp.